Leveraging Variability Modeling Techniques for Architecture Trade Studies and Analysis. Issue 1 (20th August 2013) - Ryan, Jessica; Sarkani, Shahram; Mazzuchi, Thomas
Abstract Increasing complexity in modern systems, as well as cost and schedule constraints, require a new paradigm of Systems Engineering to fulfill stakeholder needs. Challenges facing efficient trade studies include poor tool interoperability, lack of simulation coordination (design parameters), and requirements flow down. A recent trend toward Model Based Systems Engineering (MBSE) includes flexible architecture definition, program documentation, requirements traceability, and Systems Engineering reuse. As a rapidly evolving practice, MBSE still lacks governing standards and commonly accepted frameworks. This paper proposes a framework for efficient architecture definition using MBSE in conjunction with domain specific simulation to evaluate alternatives. Variant modeling techniques are introduced as an extension to capturing parameterized architecture options. Initial exploration applies such variant modeling techniques to design for adaptability trade study criteria, as a means to evaluate candidate architecture configurations against multiple requirement sets. A general framework is provided, followed with a specific example including a method for designing a trade study, defining candidate architectures, planning simulations to fulfill requirements, and designing a weighted decision analysis to optimize system objectives.